Deformation behavior and microstructure evolution in thermal-aided mesoforming of titanium dental abutment. (5th January 2016) - Meng, B.; Fu, M.W.; Shi, S.Q.
Abstract: With the increasing demand for meso/micro-scaled medical products made of biocompatible materials, thermal-aided mesoforming is proposed to improve material formability and homogenize flow behavior of materials that are difficult to deform at room temperature. However, the unique material deformation behavior and the interactive effects of material microstructure and deformation temperature on forming quality of the fabricated micropart remain unknown. This study thus aims at addressing this issue in thermal mesoforming in terms of deformation load, material flow, microstructural evolution, dimensional accuracy, and defect formation. Accordingly, the fabrication of a titanium dental abutment by one-stroke mesoforming at elevated temperature is conducted and explored. The characteristic and quality of the mesoformed part are extensively examined. The surface grains on the square extrudate undergo severe deformation and generate an equiaxed structure, reflecting that mesoforming at elevated temperature facilitates the homogenization of material flow without coarsening grain size. In addition, the dimensional accuracy, surface quality and the sizes of burr and flash are associated with the initial grain size of pure titanium, and the surface finish is improved by using fine-grained titanium. The fine-grained material is thus desirable for achieving the optimal surface quality in the thermal-aided mesoformed parts. Graphical abstract: Highlights: Thermal-aided mesoforming can fabricate multi-feature dental abutment effectively. Strain hardening of titanium follows diverse patterns at room and high temperatures. Thermal mesoforming promotes uniform material flow without coarsening grain size. Surface quality and defect formation are linked to initial material microstructure.